From cradle to classroom : a guide to special education for young children - Young, Nicholas D., 1967-; Jean, Elizabeth, 1963-; Mead, Anne E. (Rowman & Littlefield, 2018)
This book offers a comprehensive look at all that is necessary to ensure success of children with exceptionalities, birth to age 5, while understanding that typical peers will also benefit from the interventions and strategies suggested.